2022
DOI: 10.7181/acfs.2022.00150
|View full text |Cite
|
Sign up to set email alerts
|

A computed tomography-based analysis of the structure of the mandible according to age and sex

Abstract: Background: The primary objectives of mandibular surgery are to achieve optimal occlusion, low sensory disturbance, and adequate fixation with early movement. In-depth knowledge of the mandibular structure is required to achieve these goals. This study used computed tomography (CT) to evaluate the mandibular cortical thickness and cancellous space according to age and sex.Methods: We enrolled 230 consecutive patients, aged 20 to 50 years, who underwent CT scanning. The cortex and cancellous space centered arou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 34 publications
(63 reference statements)
0
1
0
Order By: Relevance
“…This suggests a possible correlation between the relatively less intense impact on the mandible and the incidence of split fractures. The thickness of the mandibular cortex decreases after the age of 35 years [ 8 ]. Yet, in this study, there appeared to be a minimal correlation between cortical thickness and split fractures, as patients in their 20s and those in their 60s and 70s exhibited similar fracture patterns.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests a possible correlation between the relatively less intense impact on the mandible and the incidence of split fractures. The thickness of the mandibular cortex decreases after the age of 35 years [ 8 ]. Yet, in this study, there appeared to be a minimal correlation between cortical thickness and split fractures, as patients in their 20s and those in their 60s and 70s exhibited similar fracture patterns.…”
Section: Discussionmentioning
confidence: 99%
“…CT or cone-beam CT (CBCT) mandibular measurements are common and have been used in orthodontic [ 17 ], temporomandibular joint [ 18 ], dental implant [ 19 , 20 ], oropharyngeal airway [ 21 ], inferior alveolar nerve [ 22 , 23 ], mandibular third molar [ 24 ], and coronoid foramina [ 25 ] studies. However, these were limited to the alveolar region [ 20 , 24 ], inferior alveolar nerve region [ 19 , 22 , 23 ], mandibular branch [ 17 , 25 , 26 ], and mandibular condyle [ 18 ]. The thickness of the mandible near the inferior margin is partly understood based on clinical experience, imaging studies [ 27 ], and anatomy [ 28 ]; however, such data are rarely reported in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…CT or cone-beam CT (CBCT) mandibular measurements are common and have been used in orthodontic [17], temporomandibular joint [18], dental implant [19,20], oropharyngeal airway [21], inferior alveolar nerve [22,23], mandibular third molar [24], and coronoid foramina [25] studies. However, these were limited to the alveolar region [20,24], inferior alveolar nerve region [19,22,23], mandibular branch [17,25,26], and mandibular condyle [18].…”
Section: Discussionmentioning
confidence: 99%
“…Choi and Hur [58] claim that the maximal value from the occlusal plane can prevent injecting too deeply, thus preventing IAN block, in contrast to using the mean value as a point of reference. Nevertheless, preoperative scanning is a crucial step for the evaluation of the structure of the mandible prior to any invasive procedures [59]. With respect to the SSRO dentofacial correction procedure, the ML provides a convenient landmark for a safe horizontal osteotomy [7].…”
Section: Discussionmentioning
confidence: 99%